"Fair to me, fair to us, or fair to you?" Unresolved conflict between government and graduates over Australia's tertiary education loans. Issue 1 (2nd January 2022) - Braithwaite, Valerie; Ahmed, Eliza; Cleland, Deborah
ABSTRACT: Australia adopted income-contingent government loans for tertiary students 30 years ago, aiming to promote greater access and equity in higher education, as repayments were required only when income exceeded a threshold. Why then does the scheme still cause dissension and with what consequences for government? We analyse qualitative and quantitative survey data to answer this question. Contrary to the government's universal conception of fairness, graduates keenly perceive unfairness relative to their peers. Our results indicate that perceptions of unfair treatment create enduring difficulties for governments in securing cooperation from their citizens.